공동주택 리모델링 초기 단계 의사결정을 위한 확률론적 리스크 기반 비용 예측 모델 개발 - 이동건; 차희성; Lee, Dong-gun; Cha, Heesung (한국건설관리학회 논문집, 17(2), 2016)
The current remodeling cost estimation process is not only dependent on the historical data of new building construction, but it also has a poor linkage with risk-based estimation approach. As such, there is a high risk of falling short of initial budget. To overcome this, a risk-based estimation approach is necessary by providing a probabilistic estimation in consideration of the potential risk factors in conducting the remodeling projects. In addition, the decision-making process should be linked with the risk-based estimation results in stead of intuitive and/or experience-based estimation. This study provides a probabilistic estimation process for residential remodeling projects by developing a detailed methodology in which a step-by-step approach can be achieved. The new proposed estimation approach can help in decision-making for remodeling projects in terms of whether to proceed or not, by effectively reflecting the potential risk factors in the early stage of the project. In addition, the study can enhance the reliability of the estimation results by developing a sustainable estimation process model where a risk-based evaluation can be accomplished by setting up the cost-risk relationship database structure. 건축 리모델링 공사비는 신축과 달리 기존 건축물이 지니는 설계제약여건과 공사환경에 따른 다양한 영향인자들(내구연한, 지반상태, 대지여건 등)에 의해 영향을 받기 마련이다. 이러한 리모델링 사업의 성공적 수행을 위해서는 의사결정과정에서 다양한 불확실성 인자들에 대한 명확한 진단이 필수적이다. 현행 리모델링 비용 견적 프로세스를 살펴보면, 과거 신축 건물의 경험치에 전적으로 의존하고 있을 뿐만 아니라, 불확실성에 입각한 체계적인 평가 방법론이 구축되어 있지 않아서 공사비 증가 등에 따른 사업 리스크가 상존해 있다. 이를 위해서는 리모델링 공사비 견적 시 리스크를 반영한 확률론적 산출 방안의 개발이 요구되고, 이를 위해 리모델링 의사결정 대안별 영향요인의 체계적인 파악을 통해 경험과 직관에 의존하는 기존 방식에서 탈피해야 할 필요가 있다. 본 연구는 공동주택 리모델링 사업의 성공적인 수행에 장애요인으로 작용하고 있는 확정적(deterministic) 견적 산출 방식을 프로젝트의 불확실성을 반영한 확률론적(probabilistic) 견적 방식으로의 전환을 위한 방법론을 구축하였다. 이를 통해 리모델링 사업 초기 개산 견적 시 프로젝트의 특성에 따른 불확실성을 반영한 예상 공사비를 산출함으로써, 발주자의 합리적인 리모델링 투자 의사결정을 지원할 수 있을 것으로 판단된다.